Blocking, Bending, and Binding: Regulation of Initiation of Chromosome Replication During the Escherichia coli Cell Cycle by Transcriptional Modulators That Interact With Origin DNA - Grimwade, Julia E.; Leonard, Alan C. (Frontiers in Microbiology, 2021)
Genome duplication is a critical event in the reproduction cycle of every cell. Because all daughter cells must inherit a complete genome, chromosome replication is tightly regulated, with multiple mechanisms focused on controlling when chromosome replication begins during the cell cycle. In bacteria, chromosome duplication starts when nucleoprotein complexes, termed orisomes, unwind replication origin (oriC) DNA and recruit proteins needed to build new replication forks. Functional orisomes comprise the conserved initiator protein, DnaA, bound to a set of high and low affinity recognition sites in oriC. Orisomes must be assembled each cell cycle. In E. coli, the organism in which orisome assembly has been most thoroughly examined, the process starts with DnaA binding to high affinity sites after chromosome duplication is initiated, and orisome assembly is completed immediately before the next initiation event, when DnaA interacts with oriC’s lower affinity sites, coincident with origin unwinding. A host of regulators, including several transcriptional modulators, target low affinity DnaA-oriC interactions, exerting their effects by DNA bending, blocking access to recognition sites, and/or facilitating binding of DnaA to both DNA and to itself. In this review, we focus on orisome assembly in E. coli. We identify three known transcriptional modulators, SeqA, Fis (Factor for inversion stimulation), and IHF (Integration Host Factor), that are not essential for initiation, but which interact directly with E. coli oriC to regulate orisome assembly and replication initiation timing. These regulators function by blocking sites (SeqA), and by bending oriC DNA (Fis and IHF) to inhibit or facilitate cooperative low affinity DnaA binding. We also examine how the growth-rate regulation of Fis levels might modulate IHF and DnaA binding to oriC under a variety of nutritional conditions. Combined, the regulatory mechanisms mediated by transcriptional modulators help ensure that at all growth rates, bacterial chromosome replication begins once, and only once, per cell cycle.